(untitled) (Contemporary Journal of Social Science Review, 2025)
Purpose: Employing the TOE (Technology, Organization, Environment) Theory as its conceptual framework, this e-learning case study highlights Jordan’s educational system. It explains the reasons for its core purpose, which is to test the hypotheses concerning the intricate links between the processes of absorbing new technologies, managing organizations, and their surroundings, as well as the efficacy of e-learning leadership. Methodology: The study incorporates a detailed research design along with appropriate sampling, customized for the education system in Jordan. Reform, with the introduction of different basic statistical techniques like regression within e-learning, evaluates the relationships of technology and organization, environment, and e-learning leadership. Findings: The study’s findings contribute to both the theoretical and practical understanding of the role of e-learning leadership in Jordan as they provide a better understanding of how these variables interact with each other. Significance: this study makes a significant contribution to improving e-learning experiences and outcomes in the area, throughout Employing a quantitative research strategy